SOME ISSUES OF IMPROVEMENT OF NORMATIVE LEGAL ACTIVITY - Asadov Eldorjon Nizomiddin o‘g‘li (Scholar Express Journals, 2022)
In this article, the author describes the characteristics of the expert review of the draft normative legal document, the economic, financial, scientific, linguistic, ecological expertise according to the decision of the developer of the draft normative legal document or the body that has the right to adopt the normative legal document. , as well as the effectiveness of conducting other types of expertise was analyzed. Theoretical and practical conclusions were developed by the author on the basis of the general statistical analysis of the expertise of the draft of the normative legal document, based on the analysis of the changes of the issues of the expertise of the draft of the normative legal document in recent years
Keywords: Legal expertise; regulatory legal documents; legislation; laws